Formulasi Dan Uji Mutu Fisik Sediaan Bedak Padat Ekstrak Biji Bunga Matahari (Halianthus Annuus L.) Sebagai Antioksidan - Ilham La Tansa; Bangkit Riska Permata; Kusumaningtyas Siwi Artini (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Sunflower (Halianthus annuus L.) is a flower that is widely consumed by the world's people. The part that is consumed from the sunflower is the seeds of the flower. Sunflower seeds have many useful ingredients in them, such as high nutritional value, being a good source of unsaturated fat, protein, inorganic compounds, vitamin E. One of the plants that has the potential as an antioxidant is sunflower (Halianthus annuus L.). The purpose of this study was to determine whether sunflower seed extract pressed powder (Halianthus annuus L.) had good physical quality, to determine whether sunflower seed extract pressed powder (Halianthus annuus L.) had antioxidant activity, to determine what concentrations of sunflower seed extract pressed powder (Halianthus annuus L.) had strong antioxidant activity as a good compact powder. Testing the antioxidant activity using the DPPH method with a positive control, namely vitamin c. The results of this study indicate that sunflower seed extract (Halianthus annuus. L) can be made into solid powder preparations, has an extract antioxidant activity of 96.78 μg/mL and has antioxidant activity when made into pressed powder preparations of 176.20 μg/mL with a concentration of 2.5%, 143.51 μg/mL with a concentration of 5%, and 121.22 μg/mL with a concentration of 7.5%.